Linkage Bank Syariah dan Fintech Syariah Penyaluran Pembiayaan Berbasis Digital dan Risiko Pembiayaan - Trimulato Trimulato (ITB AAS INDONESIA Surakarta, 2022)
The purpose this paper is to describe development financing sharia banking, then development sharia fintech services, and form linkage between sharia banking and sharia fintech distribution digital-based financing. The method used is qualitative, with a library research approach. The source data used this paper is secondary data has existed before, then been processed. Such as data from Financial Services Authority. Data collection technique used is literature from several sources are considered relevant theme. Data analysis technique used is descriptive qualitative, which describes a particular object, in this case, describes development financing sharia banking, development sharia fintech, and forms linkage can be carried out sharia banking and sharia fintech in distributing digital-based financing. Results this study indicate financing sharia banking grew 3.41 percent. Working capital financing for non-SMEs BUS decreased -7.6 percent, and non-SMEs working capital investment financing decreased -3.02 percent. Furthermore, financing at UUS experienced largest decline in working capital SMEs, which fell 10.42 percent, and non-SMEs investment fell -7.04. Financing BPRS experienced growth working capital 2.09 percent, investment 5.96 percent, and consumption 8.69. Development sharia P2P Fintech from 2020 to September 2021, total assets of P2P Fintech grew by 20.58 percent. Fintech players experienced a decline 28.19 percent. Form linkage between sharia banking and sharia fintech distribution digital-based financing, namely partnerships with profit-sharing schemes, sharia banking can channel financing through sharia fintech. It can also use Murabaha and selling to procure assets or goods. Linkage between sharia banking and sharia fintech is encouraged to increase volume non-consumptive productive financing.